Considerations for South African higher education: A 'national student men who have sex with men' sexual behaviour survey - Brink, J.G. (South African Journal of Higher Education, 2017)
This non-experimental study contributes to the quantitative knowledge about university student men who have sex with men (MSM), their sexual behaviour and their experiences on campus. A sample of 8896 students (MSM n = 896; non-MSM n = 7973) were recruited through convenience sampling in a once off online survey at fourteen higher education institutions (HEIs) in South Africa. The results indicate various risk factors for HIV transmission. These include: high partner turnover, concurrent sexual partners, presence of sexually transmitted infections, early sexual debut, having female sex partners, forced sex experiences, and inconsistent condom usage. MSM were found to have statistically higher levels of alcohol and drug use than non-MSM students. Student MSM in South African HEIs engage in sexual behaviours which elevates their risk of contracting HIV and other sexually transmitted infections. Student MSM also experience abuse or violence on campus due to their sexual preferences.